Adaptive [re]use : an investigation into the adaption of an existing building for various programmed scenarios at 116 Paul Kruger Street in the Pretoria City Centre - Botes, Nico (University of Pretoria, 2013)
Dissertation (MArch(Prof))--University of Pretoria, 2010.